2009
DOI: 10.1007/s00466-009-0431-2
|View full text |Cite
|
Sign up to set email alerts
|

Static analysis of Timoshenko beam resting on elastic half-plane based on the coupling of locking-free finite elements and boundary integral

Abstract: Making use of a mixed variational formulation including the Green function of the soil and assuming as independent fields both the structure displacements and the contact pressure, a finite element model is derived for the static analysis of a foundation beam resting on elastic half-plane. Timoshenko beam model is adopted to describe structural foundations with low slenderness and to impose displacement compatibility between beam and half-plane without requiring the continuity of the first order derivative of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 43 publications
(70 reference statements)
2
52
0
Order By: Relevance
“…Using the theorem of work and energy for exterior domains, it may be demonstrated that the total potential energy for the substrate, ∏ soil , is given by (Tullini and Tralli, 2010;Tullini et al, 2012):…”
Section: Total Potential Energy For the Substratementioning
confidence: 99%
See 4 more Smart Citations
“…Using the theorem of work and energy for exterior domains, it may be demonstrated that the total potential energy for the substrate, ∏ soil , is given by (Tullini and Tralli, 2010;Tullini et al, 2012):…”
Section: Total Potential Energy For the Substratementioning
confidence: 99%
“…In this study, the shape functions collected by matrix N a (ξ) = [N a,1 , N a,2 ] are linear Lagrangian polynomials N a,1 1-ξ and N a,2 = ξ, whereas matrix N b (ξ) assembles the "modified" Hermitian shape functions already adopted by Minghini et al (2009;2010;Tullini and Tralli, 2010;Tullini et al, 2013b).…”
Section: Finite Element Modelmentioning
confidence: 99%
See 3 more Smart Citations